Eksplorasi Mediator Potensial Perilaku dalam Adopsi Gaya Hidup Sehat pada Wanita dengan Risiko Sindrom Metabolik di Komunitas Kebugaran, Provinsi Lampung : Eksplorasi Mediator Potensial Perilaku dalam Adopsi Gaya Hidup Sehat pada Wanita dengan Risiko Sindrom Metabolik di Komunitas Kebugaran, Provinsi Lampung - Rusyantia, Anggun; Wahyuni, Endang Sri; Bertalina; Juherman, Yulia Novika (Universitas Airlangga, 2026)
Background: Metabolic syndrome (MetS) is a risk factor for Non-Communicable Diseases (NCDs). Lifestyle modifications through healthy dietary regulation and physical activity, supported by nutrition education interventions, effectively reduce the prevalence of MetS. To promote participation in lifestyle modifications, designing effective interventions requires a deeper understanding of people’s potential behavioral mediators associated with MetS. Objectives: The purpose of the study was to investigate potential behavioral mediators of healthy lifestyle adoption among adult women at risk for MetS. Methods: This study employed a qualitative-descriptive design, using semi-structured interviews to elicit in-depth perspectives from 18 participants. Thematic analysis was conducted using an inductive approach to formulate themes. Results: Participants’ understanding of MetS risks and prevention was limited. Participants had high confidence in physical exercise, but it was not yet aligned with the suggested frequency, duration, and techniques, while self-efficacy for healthy eating habits remained low. Conclusions: Participants expressed a significant need for further information and guidance on the prevention and management of MetS. Knowledge, intention, self-efficacy, and result expectations were recognized as primary internal possible behavioral mediators. A behavior-based intervention guided by Social Cognitive Theory is recommended to inform the design of contextual and effective nutrition education programs that support sustainable behavior change.